2021
DOI: 10.1001/jamaophthalmol.2021.0108
|View full text |Cite
|
Sign up to set email alerts
|

Topographical Response of Retinal Neovascularization to Aflibercept or Panretinal Photocoagulation in Proliferative Diabetic Retinopathy

Abstract: Key Points Question What is the topographic distribution of retinal neovascularization in patients with proliferative diabetic retinopathy, and is there an association between response to treatment and the retinal location of the neovascularization? Findings In this post hoc unmasked analysis of the Clinical Efficacy and Mechanistic Evaluation of Aflibercept for Proliferative Diabetic Retinopathy (CLARITY) randomized clinical trial, treatment-naive retinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Treatment naive patients with NVE demonstrated particularly greater benefit from aflibercept over PRP. The rate of neovascularization regression in these patients was 96% with aflibercept versus 78% with PRP, which was statistically significant [ 51 ].…”
Section: Comparing Anti-vegf Versus Prp As Primary Therapy For Pdrmentioning
confidence: 99%
“…Treatment naive patients with NVE demonstrated particularly greater benefit from aflibercept over PRP. The rate of neovascularization regression in these patients was 96% with aflibercept versus 78% with PRP, which was statistically significant [ 51 ].…”
Section: Comparing Anti-vegf Versus Prp As Primary Therapy For Pdrmentioning
confidence: 99%
“…As recently reviewed [ 48 ], aflibercept is commonly used in the therapy of DME patients, resulting in greater visual acuity improvement and anatomic restoration than traditional laser therapy or monoclonal antibody drugs. The recent CLARITY clinical trial demonstrated that in patients with PDR, the topographical response of retinal neovascularization to aflibercept treatment was superior to panretinal photocoagulation [ 49 ]. Regarding the pharmacokinetics (PK) of anti-VEGF treatments, the intravitreous half-life of aflibercept in humans, as predicted by a mathematical model, is approximately 7 days, which is longer than that of ranibizumab and similar to that of bevacizumab [ 50 ].…”
Section: Management Of Neovascular Retinal Diseasesmentioning
confidence: 99%
“… 84 , 89 The CLARITY study was the first randomised clinical trial of intravitreal aflibercept for PDR and its use over PRP in PDR management. 90 , 91 In the post hoc analysis of the CLARITY study, 120 treatment-naïve patients with PDR were randomly assigned to intravitreal aflibercept (2 mg/0.05 mL at baseline, 4 weeks, 8 weeks, and as needed from 12 weeks onwards) or PRP (conducted in initial fractionated sessions and reviewed every 8 weeks followed by PRP again if required). The investigation was undertaken to establish the outcome of aflibercept and PRP on NV in PDR by examining the topological response.…”
Section: Pivotal Trials Related To Use Of Anti-vegf Therapy In Pdrmentioning
confidence: 99%
“…However, it was observed that NVD was rare, although more resistant to available treatment regimens. 84 , 90 …”
Section: Pivotal Trials Related To Use Of Anti-vegf Therapy In Pdrmentioning
confidence: 99%